A typology of blood donor motivations. Issue 9 (2nd July 2020) - Ferguson, Eamonn; Hill, Alexandra; Lam, Michael; Reynolds, Claire; Davison, Katy; Lawrence, Claire; Brailsford, Susan R
Abstract: Background: Although the need for whole blood is declining, so too are the number of first‐time and repeat blood donors. To develop new recruitment and retention strategies, therefore, we need to draw on as wide a variation in blood donor motivations as possible. The primary aim of this study is to draw on a large survey of donors to develop a broad, theoretically instantiated typology of donor motivations to identify new and less common, yet practically important, motivations that have not been previously reported. Study Design and Methods: Using data from the UK Blood Donor Survey run by NHS Blood and Transplant/Public Health England Epidemiology Unit (N = 61 123 donors), we analyze fixed (N = 52 225) and free (N = 8867) responses to develop a more comprehensive typology of blood donor motivations based on theories from the biology, psychology, philosophy, economics, and sociology of altruism. Results: We identified 54 motivations, including a number of newly identified motivations, for blood donations which we organized into 12 superordinate categories (eg, "inspiration via moral elevation, " "perceived social closeness, " and "fungibility of donations"). These are linked to intervention suggestions such as donating blood in memoriam or donating blood as an alternative to other charitable acts. Conclusion: We present the most comprehensive account of blood donor motivations to‐date. This work also offers a structure for coding free‐text responses, developing motivational measures, and identifying tangible interventions. Thus, we feel that this is a valuable resource for blood donor researchers, marketers, and policy makers.